122k views
0 votes
Solve for y.

2y - x =
3
4
(-y + 1)

Solve for y. 2y - x = 3 4 (-y + 1)-example-1
User Anurag H
by
5.5k points

2 Answers

1 vote

2y-x=3/4(-y+1)first distribute

2y-x=-3/4y+3/4 get the y on one side

2y-x+3/4y=3/4 add 3/4y to both sides

2y+3/4y=3/4+x add x to both sides

11/4y=3/4+x now divide by 11/4 (both sides)

y=3/11+4/11x

y=3+4x/11

choice c is the answer

User Ragnar Lothbrok
by
5.3k points
3 votes

Answer:
\bold{C.\quad y=(4x+3)/(11)}

Explanation:


2y-x=(3)/(4)(-y+1)\\\\\\\text{Multiply both sides by 4 to clear the denominator:}\\4(2y-x)=3(-y+1)\\\\\text{Distribute:}\\8y-4x=-3y+3\\\\\text{Add 3y to both sides:}\\11y-4x=3\\\\\text{Add 4x to both sides:}\\11y=4x+3\\\\\text{Divide both sides by 11:}\\\\\boxed{y=(4x+3)/(11)}

User Kuslahne
by
5.1k points